Brizola : um percurso na imprensa no norte do Rio Grande do Sul (1961-1964) - Antunes, Clarissa (2013)
The aim of this study is to verify how it was portrayed the trajectory of Leonel Brizola, in the period 1961-1964, via the newspapers O Nacional e Diário da Manhã, that were circulating in the city of Passo Fundo, RS. In order to examine the facts as they were reproduced in the press, we will perform a brief discussion about the relationships present in the association between history and media taking into account that such discourses produced by the media reveal political positions and allow us to infer the context of the time. The research will tackle the form adopted by the passo-fundense press to report from the Legality, occurred between August 25th and September 07th, 1961, and the figure of Brizola, then governor and leader of the movement in Rio Grande do Sul, to the civil-military coup of 1964.